2016
DOI: 10.1021/acs.jpcc.6b03973
|View full text |Cite
|
Sign up to set email alerts
|

Quantum State Resolved 3D Velocity Map Imaging of Surface-Scattered Molecules: Incident Energy Effects in HCl + Self-Assembled Monolayer Collisions

Abstract: Thermal and hyperthermal HCl (v = 0, J = 0) collision dynamics at the surface of methyl-terminated self-assembled monolayers (SAMs) are probed by state-selective ionization followed by velocity-map imaging (VMI) to yield a full 2π steradian map of final 3D velocity distributions (v x , v y , v z ) as a function of rovibrational (v, J) quantum state. "DC slicing" of the scattered HCl flux normal to the surface (v z ) provides a powerful tool for eliminating incident beam contamination, as well as access to full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 72 publications
2
24
0
Order By: Relevance
“…Others have previously reported using position sensitive detection methods for studying surface scattering, 30 based on ion imaging [31][32][33] or velocity map imaging techniques, which were developed at around the same time as those for the gasphase imaging experiments. 34,35 These have predominantly used a geometry in which the surface and the detector are parallel, [36][37][38][39][40][41] which is convenient for the production of the imaging electric fields but prevents the projection of the full velocity distribution in the scattering plane onto the detector. Our new imaging setup (shown in Fig.…”
Section: Fig 2 Schematic Of Imaging Ion Optics the Ionization Lasementioning
confidence: 99%
“…Others have previously reported using position sensitive detection methods for studying surface scattering, 30 based on ion imaging [31][32][33] or velocity map imaging techniques, which were developed at around the same time as those for the gasphase imaging experiments. 34,35 These have predominantly used a geometry in which the surface and the detector are parallel, [36][37][38][39][40][41] which is convenient for the production of the imaging electric fields but prevents the projection of the full velocity distribution in the scattering plane onto the detector. Our new imaging setup (shown in Fig.…”
Section: Fig 2 Schematic Of Imaging Ion Optics the Ionization Lasementioning
confidence: 99%
“…The most robust empirical support for a dual temperature TD/IS pathway has been found in scattering studies with HCl/DCl. From time of flight studies by Nathanson and co-workers in the forward scattering direction, it was established that HCl/DCl undergoes complete thermalization and cos­(θ) desorption from several liquid surfaces. This was subsequently reinvestigated with both IR direct absorption and REMPI/VMI measurements, which confirmed that HCl/DCl at low energies equilibrates and undergoes thermal desorption in both external (translational) and internal (rotational) degrees of freedom ( T trans ≈ T rot ≈ T S ). , The REMPI/VMI studies at higher collision energies took this one step farther and showed that, due to extreme glancing incident angles (75 o ), J state populations from both TD and IS pathways could be extracted by separate analysis of the backward and forward velocity components, respectively. This permitted a novel and completely independent test of the dual-temperature TD/IS paradigm, demonstrating that the IS distributions still appear Boltzmann-like but with T IS > > T TD and yet TD distributions with T TD ≈ T S .…”
Section: Introductionmentioning
confidence: 96%
“…Prospects for controlled engineering of chemical dynamics at the gas–liquid interface require a detailed understanding of collisional molecular energy transfer, in principle, into each of the electronic, vibrational, rotational, and translational degrees of freedom. Through a multitude of elegant chemical physics/molecular beam techniques, including direct absorption laser spectroscopy, , time of flight mass spectroscopy, and resonance-enhanced multiphoton ionization (REMPI) plus velocity map imaging (VMI) platforms, collisional energy transfer between a scattering projectile and the liquid surface has indeed been extensively explored with respect to translational and rotational degrees of freedom. In remarkable contrast to the extreme molecular heterogeneity and complexity of the gas–liquid interface, empirical evidence suggests that these scattering pathways “bifurcate” into two very much simpler channels.…”
Section: Introductionmentioning
confidence: 99%